Detection of Streptococcus mutans using padlock probe based on Rolling Circle Amplification (RCA) - Mônica Moreira (Brazilian Archives of Biology and Technology, 2015)
The aim of this study was to develop and evaluate a padlock probe based on the Rolling Circle Amplification (RCA), which targeted to 16S-23S rDNA region of S. mutans. The specificity of developed padlock probe was tested for DNA within a panel strains, including S. mutans isolated from the saliva and reference strains of the genus Streptococcus, as well as total DNA samples of biofilm and saliva. The results were positive either for DNA samples of S. mutans or DNA samples recovered from the biofilm and saliva revealing the specificity of designed padlock probe. The padlock probe based on the RCA was proved to be an effective, reproducible method for S. mutansdetection and demonstrated the possibility of a rapid detection and accurate identification of S. mutans infection.